Nasu-Hakola disease: The first case reported by Nasu and review - Kaneko, Minoru; Sano, Kenji; Nakayama, Jun; Amano, Naoji (Neuropathology, 2010)
Nasu‐Hakola disease (NHD) was first reported separately by Nasu and Hakola around the same time in the 1970s. It is an autosomal recessive inherited disorder characterized by progressive dementia and repeated pathological fractures during adolescence. It has recently been demonstrated that NHD is caused by a mutation in the TREM2 or DAP12 gene. The present paper demonstrates the first patient reported by Nasu and reviews NHD. The patient was a man who died at the age 38 years. His family history was unremarkable. There was no abnormal developmental history. At the age of 26, the patient suffered a pathological fracture of the right tibia, and X‐ray confirmed bone resorption in the right tibia. As for mental status, the patient tended to be euphoric. After that, bone resorption was also seen in other long bones. At the age of 33, the patient could not walk after suffering a right femoral neck fracture. He was apathetic and exhibited behavioral abnormalities. At the age of 38, he could not move or speak and subsequently died. General pathological examination showed yellow opaque gelatinous substances in the medullary cavities, matching translucent cystic lesions in the femur, tibia, and fibula on X‐rays. Light microscopy showed numerous membranocystic changes in the substances. The brain weighed 1050 g. Symmetric systemic cerebral atrophy, in particular atrophy of the cerebral white matter in the occipital and temporal lobes, was confirmed. Histological examination showed white matter degeneration and diffuse sclerosis accompanied by astroglial proliferation. Severe demyelination was confirmed. Axonal degeneration and destruction were marked. In demyelinated areas, fat granule cells appeared, and lipid granule‐positive cells aggregated around vessels. Cerebral cortical neurons were relatively maintained. In the brain, no membranocystic lesions could be recognized. In the DAP12 gene, the patient had a conversion of nucleotide at position 116 resulting in serine 38 to asparagine substitution.